Fast Swelling Superabsorbent Hydrogels Starch Based Prepared by Gamma Radiation Techniques - Erizal Erizal; Dian Pribadi Perkasa; Basril Abbas; Sudirman Sudirman; Sulistioso G.S. (Indonesian Journal of Chemistry, 2014)
Fast swelling hydrogels were synthesized from the mixture of acrylamide (AAM)-acrylic acid (AA)-starch (15:5:1 w/v) solution by radiation crosslinking with varying irradiation doses (7.5-12.5 kGy) at room temperature. The copolymers were characterizated by Fourier transform infra red spectroscopy (FTIR) and Differential scanning calorimetry (DSC). It was found that hydrogels showed superabsorbent properties with higher swelling capacities (~400 g/g) and reached at a very short time (3 min). There was no significance difference between the effect irradiation dose on swelling of hydrogels. The hydrogels were also found to sensitive to the ionic strength of medium. The FTIR spectra and thermogram DSC of hydrogels were confirmed the crosslinking occurs in the hydrogels.